2022
DOI: 10.1177/03611981221116626
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Information and Communication Technologies and Travel Behavior: Using Behavioral Data to Explore Correlates of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has highlighted the importance of information and communication technologies (ICTs) in providing virtual engagement. Planners and engineers must determine whether cities will see reductions in travel demand, given the increasing use of ICTs. Notably, ICTs facilitate online shopping and working from home (WFH). Generally, online shopping may lead to fewer shopping trips; similarly, WFH may reduce work-related trips. However, more WFH has the potential to generate other non-work trips, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The analysis of a travel survey confirmed that online shopping reduces the number of shopping trips (changed practice effect) [57,58], but it does not increase the number of non-shopping trips (no rebound effect) [58]. Although online shopping can foster the consumption of digital services and travel (induction rebound effect), as discovered by the analysis of an online-survey by Frick and Matthies [59].…”
Section: Ict Servicesmentioning
confidence: 89%
“…The analysis of a travel survey confirmed that online shopping reduces the number of shopping trips (changed practice effect) [57,58], but it does not increase the number of non-shopping trips (no rebound effect) [58]. Although online shopping can foster the consumption of digital services and travel (induction rebound effect), as discovered by the analysis of an online-survey by Frick and Matthies [59].…”
Section: Ict Servicesmentioning
confidence: 89%
“…The observed low proportions of COVID-19 vaccinated population in non-metropolitan communities in the southern part of the state might be due to inadequate healthcare facilities in these rural areas (23). Previous studies indicated that rural communities had higher burdens of diseases in general but lower access to healthcare resources than urban communities (35)(36)(37)(38)(39). According to a report by the Missouri Department of Health, counties in the southern part of the state tended to have fewer healthcare centers and primary care providers than the state average (40).…”
Section: Discussionmentioning
confidence: 99%
“…Online purchasing, commonly called e-shopping or e-commerce, has significantly expanded recently. However, online sales experienced a remarkable surge during the COVID-19 pandemic (Ma et al, 2022;Patwary & Khattak, 2022). 'Online shopping' has burgeoned, with consumers seeking the breadth of selection and the convenience of home delivery that online platforms offer.…”
Section: 21rise Of E-commerce and Digital Servicesmentioning
confidence: 99%